2020
DOI: 10.1038/s41598-020-76995-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNA-181b-5p, miRNA-223-3p, miRNA-210-3p, let 7i-5p, miRNA-21-5p and miRNA-29a-3p in patients with localized scleroderma as potential biomarkers

Abstract: Localized scleroderma (LoSc) is a rare disease manifested by an inflammation and sclerosis of the skin. The latest studies focused on glycoprotein Krebs von den Lungen-6, surfactant protein-D, chemokine ligand 18 and dipeptidylpeptidase 4 as potential biomarkers of skin fibrosis in systemic scleroderma. Our study aimed to identify 6 miRNAs with elevated or decreased levels in 38 LoSc patients (31 females, 7 males) compared to healthy volunteers (HVs) and to correlate the selected miRNAs’ serum levels with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…Indeed, exosomes often lack housekeeping gene-coding RNA but are rich in rRNA (71) in line with our observations; future metatranscriptomic studies will establish the diversity and origin of FA EBC RNA and whether this includes miRNAs which are established biomarkers for cancer (72)(73)(74)(75), lung inflammation (76)(77)(78), and a number of autoimmune disorders (79)(80)(81).…”
Section: Microbiome and Metabolome Analysis In Ebcsupporting
confidence: 80%
“…Indeed, exosomes often lack housekeeping gene-coding RNA but are rich in rRNA (71) in line with our observations; future metatranscriptomic studies will establish the diversity and origin of FA EBC RNA and whether this includes miRNAs which are established biomarkers for cancer (72)(73)(74)(75), lung inflammation (76)(77)(78), and a number of autoimmune disorders (79)(80)(81).…”
Section: Microbiome and Metabolome Analysis In Ebcsupporting
confidence: 80%
“…These miRNA are members of the let-7 family of miRNA which have been implicated in the development of various cancers due to their role in cell proliferation, a hallmark of tumor development ( 45 47 ), however few studies to date have examined their levels or function in RA. Studies have demonstrated elevated levels in ankylosing spondylitis T-cells, with levels correlating with disease activity ( 48 ), in addition to increased levels also identified in patients with scleroderma ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, members of the miR-223 family have been associated as important regulators in the inflammatory process that occurs during early phases of wound healing, which justifies its increase in expression on day 1, when the inflammatory process of tissue repair occurs. Also, the miR-223 family is effective in increasing the activation of neutrophils after episodes of bacterial infections, and consequently, improving the course of the healing process [31,32]. The miR-34 family also seems to be PLOS ONE related to wound healing; it has been reported that several family members are up-regulated in epidermal keratinocytes during wound healing.…”
Section: Plos Onementioning
confidence: 99%